Identificación y programación de asignaturas a ofrecer en un programa de especialización - Méndez Giraldo, Germán Andrés; Caballero Villalobos, Juan Pablo; Álvarez Pomar, Lindsay (Ingeniería, 2005)
This paper presents an alternative proposal for a solution of an existing problem for specialization programs. At the beginning of each academic period, academic programs have to select and schedule diverse courses. The expected result is a timetable that offers the greatest satisfaction to students and the direction of the program. As a first approach to solve the problem, a mathematical optimization was utilized through a mixed programming model in order to decide which courses to offer.However, this approach was not successful from a practical point of view. Due to the difficulties encountered from the practical point of view, a combined use of two meta heuristics techniques was proposed. These techniques have been widely recognized by the literature because of its capacities of facing high complexity problems: genetic algorithms and tabu search. The Genetic Algorithms were used to perform the selection process of the courses to be offered during the academic period, while Tabu search was used to define the scheduling of the selected courses. The design of the met heuristics is innovative and the results were presented in a relatively short period of timefor the magnitude of the problem.